Designing Virtual, Moderated Studies of Early Childhood Development - Gijbels, Liesbeth; Cai, Ruofan; Donnelly, Patrick M.; Kuhl, Patricia K. (Frontiers in Psychology, 2021)
With increased public access to the Internet and digital tools, web-based research has gained prevalence over the past decades. However, digital adaptations for developmental research involving children have received relatively little attention. In 2020, as the COVID-19 pandemic led to reduced social contact, causing many developmental university research laboratories to close, the scientific community began to investigate online research methods that would allow continued work. Limited resources and documentation of factors that are essential for developmental research (e.g., caregiver involvement, informed assent, controlling environmental distractions at home for children) make the transition from in-person to online research especially difficult for developmental scientists. Recognizing this, we aim to contribute to the field by describing three separate moderated virtual behavioral assessments in children ranging from 4 to 13years of age that were highly successful. The three studies encompass speech production, speech perception, and reading fluency. However varied the domains we chose, the different age groups targeted by each study and different methodological approaches, the success of our virtual adaptations shared certain commonalities with regard to how to achieve informed consent, how to plan parental involvement, how to design studies that attract and hold children’s attention and valid data collection procedures. Our combined work suggests principles for future facilitation of online developmental work. Considerations derived from these studies can serve as documented points of departure that inform and encourage additional virtual adaptations in this field.